The stable relationship between crude oil price and petrol price: Evidence from multivariate GARCH models - Nguyễn, Văn Tuấn (Chiang Mai University (Chiang Mai, Thailand), 2022)
This study investigates the relationship between crude oil price and petrol price as well as their behaviour using daily U.S. price series in the period from January 11th 1988 to May 20th 2011. We find that univariate GARCH(1,1) is likely the most suitable model to measure the volatility of relative changes in the crude oil price and the petrol price. Whereas, a multivariate GARCH(1,1) model of the diagonal BEKK type is employed to analyse the conditional correlation of the two series. Although the view of asymmetrical responses in the crude oil price and the petrol price is unsupported by this study, it is evident that there is a strongly positive correlation between them in the long-run.